Impact of subclinically hypocalcemic stress on the plasma metabolomic profile of dairy goats - Jia Zhang; Dan Yang; Yafei Zeng; Kaini Guo; Jiajian Zhang; Yan Huang; Yuzhen Sui; Qimin Liu; Xiaoxuan Mo; Chenxu Zhao; Jianguo Wang (Animal Bioscience)
Objective This study aimed to explore novel aspects of disease prevention and control in Guanzhong dairy goats through the application of metabolomics and lipidomics. Methods In this study, plasma samples were collected from 96 primiparous Guanzhong dairy goats with similar body condition scores (2.75±0.15, mean±standard deviation) on the day of calving. The aim was to identify key differences in metabolite expression between diseased and healthy animals using metabolomics and lipidomics. Results Twenty-three differential metabolites and 30 differentially altered lipids were identified, which were associated with various metabolic pathways, including phenylalanine and tyrosine metabolism, aminoacyl-tRNA biosynthesis, and glycerophospholipid metabolism. Our research revealed significant differences in the regulation of calcium-related hormones and associated metabolites between subclinical hypocalcemic and healthy dairy goats. Specifically, parathyroid hormone and aspartate aminotransferase were positively correlated in the healthy group and negatively correlated in the subclinical hypocalcemic group. Conclusion The identification of phenylalanine and phosphatidylserine as potential biomarkers for subclinical hypocalcemia in dairy goats offers a novel approach to managing this condition, potentially transforming prevention and control strategies in the dairy goat industry.